Viscosupplementation as a therapeutic option for temporomandibular disorders: A literature review (Research, Society and Development, 2022)
The temporomandibular joints are considered the most important and complex joints in the human body, however, this fact does not exempt them from suffering dysfunctions, these in turn can be of muscular, skeletal or mixed origin. Several options for the treatment of these disorders have been proposed and among these is viscosupplementation, a therapeutic alternative considered minimally invasive, which consists of the injection of hyaluronic acid in the upper compartment of the temporomandibular joint, thus increasing the fluid levels. synovial This work aims to develop an informational cluster about viscosupplementation with hyaluronic acid as a form of treatment for temporomandibular disorders. In order to carry out this work, a descriptive narrative literature review was carried out using scientific articles available in the online databases BVSaluda, PUBMed, Scielo, Lilacs and Google Scholar as a bibliographic basis, these are presented in Portuguese and English. After analyzing all the material used as a bibliographic basis for the development of this work, it is concluded that viscosupplementation is shown to be a good treatment option for temporomandibular joint disorders, however it is necessary to develop a specific protocol for its execution in these joints.